Time-resolved random laser spectroscopy of inhomogeneously broadened systems - Fernandez, Joaquin; Garcia-Revilla, Sara; Carlos, Luis D.; Pecoraro, Édison [UNESP]; Arriandiaga, Maria A.; Balda, Rolindes (Wiley-Blackwell, 2014)
The understanding of energy transfer processes in biological systems occurring among optical centres which exhibit inhomogeneously broadened spectral bands is of paramount importance to determine time constants and spatial distribution of energy flow. A new time resolved-spectroscopy based on the random laser generation of the optical probes is reported. As an example, the excited state relaxation of Rhodamine B molecules in an organic-inorganic hybrid material is investigated. This kind of spectroscopy may resolve not only the spectral features of the system but also provide a high speed picture of the energy transfer and excited state relaxation of the involved optical probes. The results could be applied to other kind of efficient interacting chromophore pairs embedded in inhomogeneous scattering structures such as biological tissues.
Keywords: time-resolved luminescence; excited state relaxation dynamics; Forster resonance energy transfer; random lasers